The Correspondence of Marcin Poczobut-Odlanicki in Vilnius University Library - Girininkaitė, Veronika (Senoji Lietuvos literatūra, 2021)
Drawing inspiration from modern digital humanities research, and especially several projects related to recreating the ‘Republic of Letters’, Vilnius University Library intends to apply similar methods to the collection of letters of Marcin Poczobut (1728–1810). This article presents the process of describing, digitising, and creating a dedicated database of his letters. The initial stage of the work consists of creating descriptions of the letters. Next, the database should be made, including scanned images of the manuscripts and detailed search possibilities. It should provide better access to the manuscripts and enhance their search possibilities. On inspecting the material, we made some discoveries, attributed several letters and explored the multilingual phenomena of some of the texts, etc. The research carried out within the framework of the project will be useful for further studies in the field.
Keywords: Republic of Letters; Marcin Poczobut; astronomy; Education Commission; Enlightenment; education; history of science; Vilnius Principal School